Interkoneksitas Resouces Organization Norm Dalam Kelembagaan Agribisnis Usahatani Cabai Kelurahan Barombong Kecamatan Tamalate Kota Makassar - Bachtiar Bachtiar; Ratnawati Tahir; Jumiati Lira (Hasanuddin University, 2022)
The purpose of the study was to examine the role of agribusiness institutions in chili marketing and to analyze the R - O - N interconnectivity in the management of chili farming agribusiness institutions. Determination of informants in this study, namely the chairman of the Sukamaju Gapoktan 1 person, the chairman of the farmer group 6 people, the members of the farmer group 12 people, the chairman of the Aspartan 1 person, the wholesaler 1 person, the collector traders 2 people, the merchants the retailer traders 2 people. The analysis uses descriptive qualitative. The results showed that the role of institutional chili marketing agribusiness institutions (Gapoktan and farmer groups) in marketing is to facilitate farmers in finding market information and selling prices, Aspartan is one of the agribusiness institutions that also plays a role in selling agricultural products from farmers directly to consumers, collectors, wholesalers and retailers play a role in buying and selling (exchange function). The interconnectivity of Resources, Organization and Norm (RON) in all institutions seen in the marketing of chili agribusiness is different. Farmer-level institutions have low resources both in terms of human and financial, have a strong organization and there are rules or running values, while institutions at the wholesaler and traders level have strong resources in terms of capital, weak organization and rules of the game that are weak. unwritten, retailers have weak resources, organization and regulations. While Aspartan has strong resources, both human and financial, but there is no clear organizational structure and rules of the game.